The Use of Personal Learning Environment to Support an Online Collaborative Strategy in Vocational Education Pedagogy Course - Muchlas; Budiastuti, Pramudita; Khairudin, Moh.; Santosa , Budi; Rahmatullah , Bahbibi (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Online distance learning, on the one side, makes the learning process more efficient and flexible. However, on the other hand, it produces learning loss within a particular educational period and makes students less enthusiastic about building a collaborative attitude. In general, online learning platform providers have provided support for collaboration activity features, but in reality, they have not been able to support effective interaction. Experts believe that using the Personal Learning Environment (PLE) as an IT tool in the learning process can help create an effective online collaboration environment. This study found that PLE was proven to increase collaborative activities in online learning significantly. The reflection feature is the type of PLE that has the most significant influence on creating a good collaboration environment. The research also found that suitable collaborative activities can increase students' understanding of TVET pedagogy.